Pengaruh Pemilihan Metode Akuntansi, Auditor, Underwriter, dan Kepemilikan terhadap Tingkat Underpricing Saham - Rusmanto, Toto; Fransiska, Agnesia (Jurnal Trikonomika, 2012)
The purpose of this study is to examine the effects of accounting method choice, auditor reputation, underwriter reputation and ownership structure on the degree of underpricing. We examined 81 IPO companies listed at Indonesia Stock Exchane during 2001 to 2010 period. Using multiple regression the study found that there is no significant effect of accounting choice method, auditor reputation, underwriter and ownership structure to underpricing. This is consistent with Ali dan Hartono (2003) for inventory method choice, auditor, under writer and ownership structure. But inconsistent with Ali and Hartono (2003) for depreciation method choice.The current study classifies IPO companies from financial and non-financial, the previous research did not, this perhaps as a cause of different research result since financial and non financial companies have different characteristics and nature for fixed asset depreciations.